Scientometric Analysis of Marine and Land Resources-Based Edible Coating for Extending Shelf Life of Banana - Fauzi, Ahmat; Wullandari, Putri; Pamungkas, Amin; Siregar, Zaenal Arifin; Hakim, Arif Rahman; Bahmid, Nur Alim (The University of Lampung, 2025)
The shelf life of bananas is significantly limited due to rapid deterioration during marketing. To address this issue, edible coatings made from marine and land resources can be used in food packaging, improving consumer health, sustainability, and waste reduction in the food supply chain. Despite advancements in the field, research focusing on extending the shelf life of bananas through edible coatings remains limited. This research addresses the gap in extending banana shelf life by systematically evaluating the efficacy of edible coatings in reducing spoilage and improving preservation during marketing and storage. Employing a Systematic Literature Review (SLR) and meta-analysis with the SALSA framework, 164 scholarly journals were analyzed, highlighting 11 research clusters and 40 articles specifically discussing shelf life. Among the findings, the combination of Moringa oleifera (MO) and chitosan nanoparticles (CN) emerged as a superior combination and the most effective, extending banana shelf life by up to 30 days. This combination offers notable advantages, including strong antimicrobial properties, accessibility, cost-effectiveness, and eco-friendliness, positioning it as a practical, scalable, and sustainable approach to food preservation and waste reduction. These findings highlight the potential of innovative edible coatings to reduce food waste, support sustainability, and enhance banana supply chains. Keywords: Banana, Chitosan, Edible coating, Moringa oleifera, Review.